Antiherpes activity of glucoevatromonoside, a cardenolide isolated from a Brazilian cultivar of Digitalis lanata. - Bertol, Jessica Wildgrube; Rigotto, Caroline; Maia de Pádua, Rodrigo; Kreis, Wolfgang; Barardi, Célia Regina Monte; Braga, Fernão C.; Simões, Cláudia M. O. (Antiviral Research, 2011)
Cardiac glycosides, known ligands of the sodium pump, are widely used in the treatment of heart failure, such as digoxin and digitoxin. Besides this important activity, other biological activities, such as the antiviral activity, have been described for this group. HSV are responsible for many infections of oral, ocular and genital regions. Treatment with nucleoside analogs such as acyclovir is effective in most cases; however drug-resistance may arise due to prolonged treatment mainly in immunocompromised individuals. In this study, an antiherpes screening was performed with 65 cardenolide derivatives obtained from different sources, and one natural cardenolide, glucoevatromonoside, inhibited HSV-1 and HSV-2 replication at very low concentrations. This cardenolide showed viral inhibitory effects if added up to 12h p.i. and these effects appear to take place by the inhibition of viral proteins synthesis (ICP27, U L42, gB, gD), the blockage of virus release and the reduction of viral cell-to-cell spread. This compound also showed synergistic antiviral effects with acyclovir and anti-Na +K +ATPase activity, suggesting that cellular electrochemical gradient alterations might be involved in the mechanism of viral inhibition. These results suggest that cardenolides might be promising for future antiviral drug design. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dbio.LPB.antihe
Keywords: Antiherpes; Cardiac glycoside; Glucoevatromonoside; HSV-1